Analisis Pengembangan Ekonomi Kreatif dan Pemberdayaan Usaha dalam Meningkatkan Daya Saing Terhadap UMKM di Kabupaten Sumenep - Alan Ilahi, Nafis; Samsuki (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2023)
In Sumenep Regency, MSMEs have an important role in regional economic growth. MSMEs are the livelihood of the majority of people in Sumenep Regency. The development of MSMEs in Sumenep Regency is an important part in absorbing labor and is very productive in creating new workers, so that it can increase the number of new business units that support household income. Sumenep Regency Community. The approach used in this research is to use a quantitative method approach. The method used is the Incidental Sampling method. The aim of this research is to find out whether the development of the creative economy has an effect on increasing the competitiveness of MSMEs in Sumenep Regency. The research results show that the creative economy variable (X1) has a significant effect on the competitiveness variable (Y) and the community empowerment variable (X2) does not have a significant effect on the competitiveness variable (Y).